2006
DOI: 10.1002/adsc.200606160
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Triphenylphosphane‐3,3′,3′′‐tricarboxylate (m‐TPPTC) Ligand and Methylated Cyclodextrins: A New Combination for Biphasic Rhodium‐Catalyzed Hydroformylation of Higher Olefins

Abstract: Abstract:The methylated cyclodextrins/m-TPPTC [tris(m-carboxyphenyl)phosphane trilithium salt] couples proved to be more efficient than the wellknown methylated cyclodextrins/TPPTS [tris(m-sulfonatophenyl)phosphane trisodium salt] systems in terms of activities and selectivities to perform the Rh-catalyzed hydroformylation of higher olefins in an aqueous-organic system. The interactions cyclodextrins/m-TPPTC have been fully studied by NMR spectroscopy.Keywords: cyclodextrin; hydroformylation; phosphane; rhodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Using m -TPPTS, only 2% conversion was seen after 3 h in the hydroformylation of 1-octene at 80 °C. In contrast, m -TPPTC gave 94% conversion with 87% aldehyde selectivity under the same conditions . With 1-decene, m -TPPTC gave only 16% conversion, however.…”
Section: Catalytic Applications Of Hydrophilic Ligandsmentioning
confidence: 85%
See 1 more Smart Citation
“…Using m -TPPTS, only 2% conversion was seen after 3 h in the hydroformylation of 1-octene at 80 °C. In contrast, m -TPPTC gave 94% conversion with 87% aldehyde selectivity under the same conditions . With 1-decene, m -TPPTC gave only 16% conversion, however.…”
Section: Catalytic Applications Of Hydrophilic Ligandsmentioning
confidence: 85%
“…In contrast, m-TPPTC gave 94% conversion with 87% aldehyde selectivity under the same conditions. 442 With 1-decene, m-TPPTC gave only 16% conversion, however. Surface tension studies showed that m-TPPTC behaved as a surfactant with a CMC of approximately 0.01 M, which may account for the higher activity of catalysts derived from m-TPPTC compared to m-TPPTS.…”
Section: Strategies For Hydroformylation Of Higher Olefinsmentioning
confidence: 99%
“…This property has been studied in aqueous systems, and it is commonly accepted that the principal factors involved in binding are van der Waals and hydrophobic interactions between the host β-CD cavity and the guest molecule, even if hydrogen bonding and steric effects may be present . The capability of forming host−guest supramolecular complexes with CDs has been used in hybrid hydrocarbon/water systems to dramatically enhance the rate of mass transfer-controlled chemical reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…20) in Rh-catalyzed olefins hydroformylation were notably higher (increased by a factor of 47, 21, and 16 for 1-octene, 1-decene, and 1-dodecene, respectively) [82]. The surface activity of m-TPPTC might be responsible for its higher efficiency in the hydroformylation reaction.…”
Section: Amphiphilic Ligandsmentioning
confidence: 98%